Textbooks evaluation by Ur’s Theory - Siska Cahyani; Satya Perdana (Journal of English Language and Pedagogy, 2019)
The objectives of this study are to: (1) describe the appropriateness of textbooks used by seventh grade junior high school with the criteria of good textbooks developed by Ur’s theory, and (2) reveal the strengths and weaknesses of each textbook. This research was conducted using evaluation research. The data was obtained through document analysis and interviewing expert. Ur’s theory was used to analyze the data. The objects of this research for analysis were two English textbooks; WERB and Bright for seventh grade junior high school. The research found out When English Ring a Bell meets eight criteria of a good textbook by Ur. They are: objectives explicitly laid out in an introduction, attractive layout and visual material, interesting and various topics, the content organization, and graded adequate guidance for the teacher, and readiness of the textbook. Bright meets all the criteria of a good textbook. The researcher also found the strength of WERB lies in its colorful and attractive layout and the textbook also presents various topics that motivate the students to practice actively. There is teachers’ book as guidelines. Meanwhile, the strength of Bright lies in clear layout, pictures and illustration, four skills are covered. Its main weaknesses are the dull color of this textbook and no teacher’s book is provided. The researcher concludes that Bright is better than WERB. This book is appropriate with criteria of good textbooks and used by teacher and student. It is available in many bookstores. Bright is also compatible in terms of coherence and unity of ideas among units and language content.